Cotton soot derived carbon nanoparticles for NiO supported processing temperature tuned ambient perovskite solar cells - Shubhranshu Bhandari (Nature Portfolio, 2021)
Abstract The emergence of perovskite solar cells (PSCs) in a "catfish effect" of other conventional photovoltaic technologies with the massive growth of high-power conversion efficiency (PCE) has given a new direction to the entire solar energy field. Replacing traditional metal-based electrodes with carbon-based materials is one of the front-runners among many other investigations in this field due to its cost-effective processability and high stability. Carbon-based perovskite solar cells (c-PSCs) have shown great potential for the development of large scale photovoltaics. First of its kind, here we introduce a facile and cost-effective large scale carbon nanoparticles (CNPs) synthesis from mustard oil assisted cotton combustion for utilization in the mesoporous carbon-based perovskite solar cell (PSC). Also, we instigate two different directions of utilizing the carbon nanoparticles for a composite high temperature processed electrode (HTCN) and a low temperature processed electrode (LTCN) with detailed performance comparison. NiO/CNP composite thin film was used in high temperature processed electrodes, and for low temperature processed electrodes, separate NiO and CNP layers were deposited. The HTCN devices with the cell structure FTO/c-TiO2/m-TiO2/m-ZrO2/high-temperature NiO-CNP composite paste/infiltrated MAPI (CH3NH3PbI3) achieved a maximum PCE of 13.2%. In addition, high temperature based carbon devices had remarkable stability of ~ 1000 h (ambient condition), retaining almost 90% of their initial efficiency. In contrast, LTCN devices with configuration FTO/c-TiO2/m-TiO2/m-ZrO2/NiO/MAPI/low-temperature CNP had a PCE limit of 14.2%, maintaining ~ 72% of the initial PCE after 1000 h. Nevertheless, we believe this promising approach and the comparative study between the two different techniques would be highly suitable and adequate for the upcoming cutting-edge experimentations of PSC.